Community perception and preventive practices regarding malaria in low-endemicity regions on Indonesian Kalimantan border adjacent to high-endemicity zoonotic malaria in Malaysian Borneo - Diana, Natalia; Willy, Handoko; Sari, Rahmayanti; Tri, Rahmayanti; Khamisah, Abdul Kadir; Zulkarnain, M. Idris; Ayu Akida, Abdul Rashid; Paul Cliff, Simon Divis (BioMed Central (BMC), part of Springer Nature, 2025)
Background Indonesia aspires to completely eliminate malaria by 2030. Malaria cases have fallen drastically due to the implementation of national strategic plans and policies, and the Ministry of Health has granted certification of elimination status to various areas, including Kalimantan. However, this low prevalence contrasts sharply with the continued high prevalence (18.9%, totalling 3290 cases) of Plasmodium knowlesi infections in Malaysian Borneo. Assessing the knowledge and preventive practices regarding malaria and attitudes towards zoonotic malaria within communities along the Kalimantan border is essential to understanding the low endemicity (API < 1) of malaria in this region. Methods Between February and April 2021, a structured questionnaire was administered to respondents who lived in villages with recent malaria cases (P. vivax and P. falciparum infections) across the West, East, and North Kalimantan provinces bordering Malaysian Borneo. The questionnaire collected demographic information, knowledge, prevention practices, illness management, and attitudes towards contributing factors of zoonotic malaria. Data were analysed using descriptive statistic and the association between variables was determined using logistic regression. A P value less than 0.05 was considered statistically significant. Results Of the 639 respondents, 47.6% had completed primary education, and 49.1% worked in the agricultural sector. More than half of the respondents had good knowledge (58.2%) and good practice (51%) regarding malaria's cause, symptoms and prevention. A notable 58.9% could identify at least two classic symptoms of malaria (fever and shivering), and 78.6% associated the disease with mos quito bites. More than half of the respondents (53.7%) owned bed nets and stated using them every night on a regular basis (49.3%). However, more than half of these bed nets were not insecticide-treated. Indoor residual spraying by the health authority was uncommon. A common practice was that 84% of respondents sought treatment at health facilities when suspecting malaria (fever and shivering). Regarding the potential for acquiring zoonotic malaria, 36.2% of respondents lived near the forest, and 15.8% reported encountering monkeys within 500 m of their house. Multivariate analysis showed that an increase in education level significantly predicted good knowledge of malaria. Meanwhile, good malaria practices were significantly associated with women (aOR = 2.25; P < 0.001), age 25–64 (aOR = 2.64; P < 0.001), and age over 65 (aOR = 3.06; P = 0.004). Conclusions This study observed an exceptional level of malaria awareness among these communities. However, it is crucial to emphasise the importance of continuous malaria surveillance within this community for maintaining the current low malaria cases and achieving the goal of malaria-free status in the country by 2030.